2022
DOI: 10.3390/cancers14092193
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Spinal Instrumentation on Neurological Outcome in Patients with Intermediate Spinal Instability Neoplastic Score (SINS)

Abstract: Background: Adequate assessment of spinal instability using the spinal instability neoplastic score (SINS) frequently guides surgical therapy in spinal epidural osseous metastases and subsequently influences neurological outcome. However, how to surgically manage ‘impending instability’ at SINS 7–12 most appropriately remains uncertain. This study aimed to evaluate the necessity of spinal instrumentation in patients with SINS 7–12 with regards to neurological outcome. Methods: We screened 683 patients with spi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…The current study did not show any association of SINS or surgical procedures with the survival period. SINS is an important scoring system to assess spinal instability and determine the need for fusion surgery [ 29 ]; however, it may not predict the survival after palliative surgery based on the results of the current study.…”
Section: Discussionmentioning
confidence: 98%
“…The current study did not show any association of SINS or surgical procedures with the survival period. SINS is an important scoring system to assess spinal instability and determine the need for fusion surgery [ 29 ]; however, it may not predict the survival after palliative surgery based on the results of the current study.…”
Section: Discussionmentioning
confidence: 98%
“…[27] Although the optimal cutoff value for the need for fusion surgery has not been reached consensus, it is generally divided into 3 categories: stable (0-6 points), impending/potentially unstable (7-12 points), and unstable (13-18 points). With the worldwide recognition of SINS, spine surgeons or oncologists become to determine the application of fusion procedures by the score of SINS [28,29].…”
Section: Discussionmentioning
confidence: 99%
“…For patients with impending instability (intermediate SINS score of 7-12), the decision of performing surgical stabilization is often difficult. Lenschow et al [57] reviewed 331 spinal metastasis patients with intermediate SINS and found no significant differences in neurological outcomes between instrumented and noninstrumented patients. However, an increase in surgical complications was noted in the instrumented group [57].…”
Section: Surgical Indicationsmentioning
confidence: 99%
“…Lenschow et al [57] reviewed 331 spinal metastasis patients with intermediate SINS and found no significant differences in neurological outcomes between instrumented and noninstrumented patients. However, an increase in surgical complications was noted in the instrumented group [57]. Kim et al [58] suggested that surgical stabilization should be performed in patients having >50% vertebral body collapse with intermediate SINS.…”
Section: Surgical Indicationsmentioning
confidence: 99%